Which Factors Associated With Activated Eosinophils Contribute to the Pathogenesis of Aspirin-Exacerbated Respiratory Disease? - Choi, Youngwoo (Allergy Asthma Immunol Res, 2018)
Eosinophils have long been recognized as a central effector cell in the lungs of asthmatic patients. They contribute to airway inflammation and remodeling through releasing several molecules such as cytokines, granule proteins, lipid mediators and extracellular traps/vesicles. Repeated evidence reveals that intense eosinophil infiltration in upper and lower airway mucosae contributes to the pathogenesis of aspirin-exacerbated respiratory disease (AERD). Persistent eosinophilia is found to be associated with type 2 immune responses, cysteinyl leukotriene overproduction and eosinophil-epithelium interactions. This review highlights recent findings about key mechanisms of eosinophil activation in the airway inflammation of AERD. In addition, current biologics (targeting type 2 immune responses) were suggested to control eosinophilic inflammation for AERD patients.